Exhaled carbon monoxide: a non-invasive biomarker of short-term exposure to outdoor air pollution - Herve Lawin; Lucie Ayi Fanou; Vikkey Hinson; Jacqueline Wanjiku; N. Kingsley Ukwaja; Stephen B Gordon; Benjamin Fayomi; John R Balmes; Parfait Houngbegnon; Euripide Avokpaho; Ambaliou Sanni (BMC, 2017)
Abstract Background In urban settings of Africa with rapidly increasing population, traffic-related air pollution is a major contributor to outdoor air pollution (OAP). Although OAP has been identified as a leading cause of global morbidity and mortality, there is however, lack of a simple biomarker to assess levels of exposure to OAP in resource-poor settings. This study evaluated the role of exhaled carbon monoxide (exhCO) as a potential biomarker of exposure to ambient carbon monoxide (ambCO) from OAP. Methods This was a descriptive study conducted among male commercial motorcycle riders in Cotonou - the economic capital of Benin. The participants' AmbCO was measured using a portable carbon monoxide (CO) data logger for 8 h during the period of their shift. ExhCO was measured just before and immediately after their shift (8-h) Participants were asked not to cook or to smoke during the day of the measurements. Linear regression analysis was used to assess the association between ambCO and exhCO for the last 2, 4 and 6 h of their shift. Results Of 170 participants who completed the study, their mean ± SD age was 42.2 ± 8.4 years, and their mean ± SD daily income was 7.3 ± 2.7$. Also, 95% of the participants' used solid fuels for cooking and only 2% had ever smoked. Average exhCO increased by 5.1 ppm at the end of the shift (p = 0.004). Post-shift exhCO was significantly associated to ambCO, this association was strongest for the last 2 h of OAP exposure before exhCO measurement (β = 0.34, p < 0.001). Conclusion ExhCO level was associated with recent exposure to ambCO from OAP with measurable increase after 8 h of exposure. These findings suggest that ExhCO may be a potential biomarker of short-term exposure to OAP.